High-entropy spinel oxide: Synthesis and photo-responsivity of Mn0.68Cr0.8Rh0.64Co0.87O4 - Cho, Hyeon Ho; Yang, Juhee; Kim, Jong Kyu; Kim, Myung Hwa; Yu, Hak Ki (Journal of Alloys and Compounds, 2025)
Recently, there has been extensive research on modulating band structures using MnCr2O4, which has gained significant attention as a photocatalyst. However, due to thermodynamic constraints, conventional modulation of band structures using two compositions poses challenges. Therefore, we utilized a high-entropy approach to easily modulate band structures by forming multi-composition systems (three-composition oxides or higher). The spinel structure of Mn0.68Cr0.8Rh0.64Co0.87O4 produced via electrospinning enabled the fabrication of nano fibers with an average diameter of 160 nm at a calcination temperature of 900 °C, and these nano fibers were crystallized through various analytical instruments. Furthermore, nanofibers calcined at 900 °C exhibited high responsivity and fast rise, decay times under a light source with a wavelength of 635 nm. Thus, with such high reactivity, fast response time, and clear selectivity, Mn0.68Cr0.8Rh0.64Co0.87O4 indicates promising potential as a material for future photo-catalytic research.
Keywords: Composition systems; Entropy approach; Entropy methods; High entropy method; Multi-composition system; Nano fiber; Oxides synthesis; Photoresponsivity; Spinel oxide; Thermodynamic constraints; Band gap; High entropy method; MnCr2O4; Multi-composition systems; Photodetector